Reflections and collective production about being a municipal health counselor - Angela Maria Gomes; Liane Colliselli; Maria Elisabeth Kleba; Valéria Silvana Faganello Madureira
ABSTRACT Objective: to identify the participation dynamics of a municipal council and to develop a critical-reflexive process on "being a counselor", identifying weaknesses and possibilities of this council, in addition to collectively generating new knowledge and (re)elaborating the MHC Ordinary Law. Method: Convergent care research, including documentary analysis, non-participant observation and thematic workshops. The research was carried out in 2016, with municipal health counselors from a city in the Western Region of Santa Catarina. Results: this study made it possible to identify forms of social participation that should be strengthened in the performance of social power, to reflect and share individual experiences, to anchor them in the current legislation, and to build knowledge that enabled the elaboration/organization of a product - a new text for the Ordinary Law of the Council, adjusted to current legislation. Final considerations: There is a need to increase participation, considering the presence of the counselors in the meetings, the effective representation and a greater interaction in the discussions and deliberations of the council.